Associations Among Intrapartum Interventions and Cesarean Birth in Low‐Risk Nulliparous Women with Spontaneous Onset of Labor. (17th June 2019) - Iobst, Stacey E.; Bingham, Debra; Storr, Carla L.; Zhu, Shijun; Johantgen, Meg
Abstract : Introduction: Cesarean birth rates vary widely across hospitals in the United States, even among women who are considered low‐risk for the procedure. This variation has been attributed to differences in health care provider practice, but few studies have explored patterns of labor management in relation to cesarean birth. Methods: This was a retrospective observational study of 26, 259 nulliparous, term, singleton gestation, vertex presentation births following spontaneous onset of labor. Births occurred from 2002 to 2007 in 11 hospitals in the Consortium on Safe Labor. Generalized linear mixed modeling was used to examine the relationship between intrapartum interventions (amniotomy, epidural analgesia, oxytocin augmentation) used individually and in combination and the outcome of cesarean birth. Results: More than 90% of the women in this low‐risk sample received at least one intervention regardless of mode of birth. Epidural analgesia was the most frequently applied intervention, both when used as a single intervention (18.7%) and in combination with other interventions (79.9%). The strongest associations between these interventions and cesarean birth were observed when 2 or 3 interventions were applied during labor. Compared with women who received no interventions, the strongest association was observed among women who received amniotomy‐oxytocin augmentation (adjusted odds ratio [aOR], 1.89; 95% CI, 1.36‐2.62). The use of all 3 interventions (amniotomy‐epidural analgesia‐oxytocin augmentation) showed a similar positive association with cesarean birth (aOR 1.83; 95% CI, 1.50‐2.21). Discussion: Findings show that the combined use of amniotomy, epidural analgesia, and oxytocin augmentation is positively associated with cesarean birth. Additional research is needed to examine the timing and sequence of interventions as well as whether a causal relationship exists between combinations of interventions and cesarean birth in low‐risk nulliparous women.